2012
DOI: 10.1007/s10086-011-1244-4
|View full text |Cite
|
Sign up to set email alerts
|

Progress of oxidation of non-phenolic lignin moiety in an oxygen bleaching process via the conversion of non-phenolic into phenolic lignin moiety

Abstract: To examine whether non-phenolic lignin moiety is converted into the new phenolic counterpart by the participation of active oxygen species (AOS) under oxygen bleaching conditions, a b-O-4 type dimeric lignin modelwas treated under conditions similar to those for oxygen bleaching. A phenolic compound, 4-hydroxy-3-methoxybenzyl alcohol, was added together to generate AOS in the reaction of compound I or IV. The results obtained suggested that AOS attack the side chains of compounds I, III, and IV accompanied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
0
16
0
1
Order By: Relevance
“…Compound 1 is quite stable without oxygen under otherwise the same conditions [35]. A non-phenolic lignin model compound such as compound 1 is not directly attacked by molecular oxygen but by AOS generated in either system accompanying the reaction between molecular oxygen and a co-existing phenolic compound, TMPh or Valc, which is the generator of AOS [32,35]. A major AOS is negatively charged oxyl anion radical (O⋅), the conjugate base of hydroxyl radical (HO⋅), in either of the O 2 -TMPh or O 2 -Valc system before TMPh or Valc, respectively, disappears from the system owing to the high pH levels [32].…”
Section: Description Of the O 2 -Tmph Or O 2 -Valc Systemmentioning
confidence: 77%
See 4 more Smart Citations
“…Compound 1 is quite stable without oxygen under otherwise the same conditions [35]. A non-phenolic lignin model compound such as compound 1 is not directly attacked by molecular oxygen but by AOS generated in either system accompanying the reaction between molecular oxygen and a co-existing phenolic compound, TMPh or Valc, which is the generator of AOS [32,35]. A major AOS is negatively charged oxyl anion radical (O⋅), the conjugate base of hydroxyl radical (HO⋅), in either of the O 2 -TMPh or O 2 -Valc system before TMPh or Valc, respectively, disappears from the system owing to the high pH levels [32].…”
Section: Description Of the O 2 -Tmph Or O 2 -Valc Systemmentioning
confidence: 77%
“…Although we previously confirmed that the β-O-4 bond of compound 1 cleaves and a small amount of guaiacol is liberated in the O 2 -Valc system [35], almost no guaiacol was detected in the O 2 -TMPh system. Guaiacol is commonly oxidized by molecular oxygen.…”
Section: Degradation Products In the O 2 -Tmph Systemmentioning
confidence: 99%
See 3 more Smart Citations